ERP Service for Small and Medium Enterprises in Saudi Arabia - Arif Bramantoro (Institute of Advanced Engineering and Science, 2018)
This paper aims to present the benefits of enterprise resource planning (ERP) service over traditional ERP through the development of ERP in the form of software-as-a-service(SaaS). This service is published in response to the fact that traditional ERP is rarely implemented in small and medium enterprises (SMEs) in Saudi Arabia due to the highcost and risk of implementation failure. This paper can be used to encourage SMEs in Saudi Arabia to exploit ERP service. ERP service can be accessed by client via anyprogramming interface over an Internet connection without special configuration, thus highlighting the core competencies of the SMEs. As a prove of concept, the stock serviceis published as a concrete ERP service. Two types of application were developed to access the service: desktop and smartphone based application. Based on a simple qualitativeassessment, it is acknowledged that ERP service is advantageous over traditional ERP systems in terms of its scalability, agile implementation, global accessibility,mobility, low operational costs, lack of upfront costs, best practices, rapid upgrading, and interoperability among other services.